Peningkatan Manajemen Keuangan UMKM Melalui Pelatihan dan Perhitungan Laba Bersih - Melania Putri Baga (Universitas 45 Surabaya, 2025)
Financial management is important in the development of MSMEs, but MSMEs still often experience problems related to good financial management and management. This problem often hinders the development of MSMEs themselves. In running a business, it is very important to understand the concept of production cost preparation thoroughly. Good financial management is very beneficial for MSMEs. With neat financial records, MSMEs can understand their financial condition and monitor business development effectively. This community service activity aims to assist MSME Actors in order to manage their finances so as not to mix business finance with personal finance and also to assist MSME Actors in making financial reports in order to obtain accurate profits, namely at the Chikal 02 food stall and also the Ibu Restaurant, Maguwoharjo, Depok, Sleman, Yogyakarta. This activity will be carried out on October 12-November 29, 2024. This activity was carried out in several stages including: 1) Survey 2) Implementation and 3) Results and Evaluation. The result of this service and mentoring is an increase in understanding related to managing finances and calculating the cost from 5% to 70%, so it can be concluded that this assistance has succeeded in providing assistance in dealing with problems faced by MSME actors. This activity has brought significant improvements, improving the ability of MSME actors to prepare financial statements and be able to manage finances well.